Persistent pupillary membrane type 2 - Ramatchandirane, Balamurugan; R Patil, Goudappagoud R.; S.N. Prasad, Shubhangi (Digital Journal of Ophthalmology, 2026)
A 31-year-old woman presented AIIMS Mangalagiri with bilateral, type 2 persistent pupillary membrane (PPM) that originated from the inferotemporal region of the collarette of the iris in the right eye and the lateral half of the collarette of the iris in the left eye. Both PPMs were adherent to the lens capsule. Her best-corrected visual acuity was 6/9 in the right eye and 6/18 in the left eye. Intraocular pressure was normal in each eye. After dilation, there was a radial opacity in the lens seen at 5 o'clock in the right eye and a similar opacity was seen at 7 o’clock in the left eye.